Faktor-faktor yang BerhubungandenganKetepatan Diagnosis Bidan Dalam Merujuk Pasien Kasus Kehamilan dan Persalinan Risiko Tinggi Ke RSUD Arifin Achmad Provinsi Riau Tahun 2014 - Desmariyenti .; Nurlisis Nurlisis (STIKes Hang Tuah Pekanbaru, 2015)
Diagnosis accuracy is the diagnosing accuracy of the one case which is assigned by the medical worker and have filled the diagnosis nomenclature standart. A midwife operated the pragnancy rifering and high risk childbirth to general hospital of Arifin Achmad of Riau in 2014 about 210 cases, and not accurance in dignosing about 35 cases (17%). The reseach aims to determine the factors relating with the midwife’s diagnosis accurancy in rifering he pragnancy case patient and high risk childbirth, that is knowledge, attitude, competency, years of service, and midwife pomegranate. The used research was observasional analitic quantitative with the analitic crossectional study). The data analysis was operated as univariate, bivariate by chi square test, and multivaroate by the double logistic regression test with sample ammount about 120 people which were totally taken population. The research result which is related by midwife’s diagnosis accuracy in rifering the pragnancy case patient and high risk childbirth are knowledge (OR:4,656; 95%CI: 1,200-18,064), competence (OR:11,834; 95%CI: 1,371102,141), and years of service (OR:10,887; 95%CI: 2,657-44,602).As well as suggested the midwives follow APN training, having the optimal years of service and skill in manging the pragnancy case and high risk childbirth, and following the colloquy, workshop, training, or program which can increase the sciences esspecially accurancy in diagnosing the pragnancy and high risk childbirth.